1278 The Impact of Private Sector Cosmetic Surgery Complications on an NHS Plastic Surgery Service During the COVID-19 Second Wave: A Case Series. (12th October 2021) - Magness, C; Forsyth, M; Hasham, S; O'Boyle, C
Abstract: Introduction: COVID-19 has demanded a dramatic reorganisation of plastic surgery services. Operating within the NHS has largely been scaled back to emergency and cancer work, with elective services either on hold or transferred to independent hospitals. During this time, with NHS resources critically stretched, a number of patients presented with serious complications of private sector aesthetic surgery, which required emergency NHS treatment. This series characterises the nature and outcome of these cases. Method: A retrospective audit of patients referred to a UK Plastic Surgery Unit with complications arising from private aesthetic surgery performed during the Second Wave of Covid-19 in 2020. Results: Eight patients presented. Two had surgery in the UK, five in Turkey and one in Lithuania. The primary procedures were abdominoplasty (n = 6), liposuction (n = 5). Presenting complications were Infection (n = 5) and wound dehiscence (n = 5). Two patients presented in septic shock and one developed necrotising panniculitis. One patient suffered perioperative death due to myocardial infarction. Mean hospital stay was 10 days (range 1-31) and median number of NHS surgical procedures was 2.5 (range 0-8). Three patients required removal of breast implants; four required topical negative pressure dressings and three underwent skin grafting. Up to 7 outpatient appointments were required per patient. All survivors have unsatisfactory aesthetic outcomes. Conclusions: This case series raises important questions about the safety of major aesthetic surgery and "cosmetic tourism" during periods when the NHS' ability to deal with severe complications may be severely limited.